Syngas Production via Methane Dry Reforming over La-Ni-Co and La-Ni-Cu Catalysts with Spinel and Perovskite Structures - Sébastien Thomas; Samira Slyemi; Akila Barama; Hassiba Messaoudi; Abdelhamid Djaidja (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
In this paper, the catalytic properties of La-Ni-M (M = Co, Cu) based materials in dry reforming of methane (DRM) for syngas (CO + H2) production, were studied in the temperature range 773−1073 K. The LaNi0.9M0.1O3 and La2Ni0.9M0.1O4 (M = Co, Cu and Ni/M = 0.9/0.1) catalysts were prepared by partial substitution of Ni by Co or Cu using sol-gel method then characterized by XRD, H2-TPR and N2 physisorption. The XRD analysis of fresh catalysts showed, in the case of Co-substitution, the formation of La-Ni and La-Co perovskite and spinel structures, while only LaNiO3 and La2NiO4 phases were observed for the Cu-substituted samples. The substitution of these two structures by copper decreases the reduction temperature compared to cobalt. The reactivity results showed that the partial substitution of nickel by copper decreases the methane activation temperature, whereas a better stability of catalytic activity and syngas production was obtained via the cobalt-substituted catalysts, which is due to a synergistic effect between Ni and Co. The TPO analysis carried out on the spent catalysts indicated that the lowest carbon deposition was obtained for the cobalt substituted samples. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).